Empowerment key factors in shaping women's awareness of household waste management - D. Asteria; J. Haryanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Empowering activities is the key in building awareness and individual capacity of household waste management, especially for women as the main actors. This study aimed to explore empowering activities as the key factor in shaping women's awareness of household waste management. METHODS:This study was conducted using quantitative methods. The data collection technique used was survey. The sampling was carried out by purposive sampling technique. The criteria for sampling were those women who attended training in waste management in Jagakarsa Sub District, South Jakarta, Indonesia. The analytical technique used was Ordinary Least Square regression. FINDINGS: Based on the findings of this study, it was known that women who had good adaptability to technology were likely to have a greater chance score of 0.908. Education in schools was also found to have a positive impact on the opportunity score  to earn good living environment. It was found that an increase in 1 year of schooling will increase the score of chance by 0.0755 (estimation 5). This is not significantly different from estimation 4 which would increase the chance by 0.0745. In waste management training, The womens’ participation are likely to increase the score chance of having a good environment by 0.944 points (estimation 5). Besides, the womens’ participation were found to be statistically significant at 95% confidence level in all estimations, particularly in the waste management training. Based on the comparison of the participation coefficient parameters in waste management training, it was found that there were no significant differences or signs (+ and -) between the estimations. All coefficient parameters ranged from 0.83 to 0.94. CONCLUSION: Empowerment activities that utilize access to education and easily adapt to a technology might have a significant correlation with women's involvement in waste management training. This is the basis for building awareness to carry out more sustainable household waste management and achieve change to get a good living environment.  ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================